A floating self-propelling liquid marble containing aqueous ethanol solutions. Issue 122 (24th November 2015) - Ooi, Chin Hong; van Nguyen, Anh; Evans, Geoffrey M.; Gendelman, Oleg; Bormashenko, Edward; Nguyen, Nam-Trung
Abstract : We report the behaviour of a self-propelling liquid marble containing an aqueous ethanol solution. Abstract : A liquid marble is a droplet coated with hydrophobic particles. A floating liquid marble is a unique reactor platform for digital microfluidics. The autonomous motion of a liquid marble is of great interest for this application because of the associated chaotic mixing inside the marble. A floating object can move by itself if a gradient of surface tension is generated in the vicinity of the object. This phenomenon is known as the Marangoni solutocapillary effect. We utilized a liquid marble containing a volatile substance such as ethanol to generate the solutocapillary effect. This paper reports a qualitative study on the operation conditions of liquid marbles containing aqueous ethanol solutions in autonomous motion due to the Marangoni solutocapillary effect. We also derive the scaling laws relating the dynamic parameters of the motion to the physical properties of the system such as the effective surface tension of the marble, the viscosity and the density of the supporting liquid, the coefficient of diffusion of the ethanol vapour, the geometrical parameters of the marble, the speed, the trajectory and the lifetime of the autonomous motion. A self-driven liquid marble has the potential to serve as an effective digital microfluidic reactor for biological and biochemical applications.